Formulación poética de la persecución y el activismo: Néstor Perlongher en el Frente de Liberación Homosexual argentino. - Cid, Jorge (Nomadías)
In this article I analyze the role of Néstor Perlongher as a poet and activist in the creation of the Argentine Homosexual Liberation Front and his magazine Somos. In particular, I reflect on the poetic reformulation of his experience as an activist and victim of homophobic police repression. I also evaluate the dialogue between his poetry published in Somos and the one that appears later in his author's books, in light of his commitment to the causes that animated his political work. This study highlights the affective-political ties that poetry built with the readers of Somos and the coherence between vital acts and poetic sayings.